Beyond HAZOP: Analyzing common cause and system scenarios. Issue 2 (15th October 2018) - Roche, Eloise; Dupont, Watson; Summers, Angela
Abstract : A production operation often consists of multiple unit operations, supported by plant‐wide services such as instrument air, power, electronic communications, and cooling water. The production operation can be covered by multiple risk studies, which divide up the production operation based on nontechnical reasons, such as unit management, study length, and convenience. The use of multiple studies is particularly common with large production units or with integrated packaged equipment. The "divide and conquer" approach to the studies is good for planning and execution, but the resulting "pieces and parts" analysis can allow significant common cause scenarios to get lost in the clutter. Traditional HAZOP approaches generally focus on pairing individual causes with deviations and consequences. This traditional approach can result in inadequate consideration of more complex scenarios, such as those involving: Multiple automated system actions Global loss of service Transference of risk These complex scenarios are often interrelated and thus are not well suited for analysis by HAZOP procedures that mandate a single cause‐consequence relationship. This article will propose extensions to the typical HAZOP process to address these challenges in a more holistic manner. © 2018 American Institute of Chemical Engineers Process Saf Prog 38: e11997, 2019